Generalized separation of variables and exact solutions of nonlinear equations - Barannyk, T. A.; Barannyk, A. F.; Yuryk, I. I. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We consider the generalized procedure of separation of variables of the nonlinear hyperbolic-type equations and the Korteweg - de Vries-type equations. We construct a wide class of exact solutions of these equations which cannot be obtained with the use of the S. Lie method and the method of conditional symmetries.